A real world experience with fingolimod in active RRMS patients naïve to second-line agents: a 2 years, intention-to-treat, observational, single center study. Issue 1 (December 2016) - Baroncini, D.; Zaffaroni, M.; Annovazzi, P.; Baldini, S.; Bianchi, A.; Minonzio, G.; Comi, G.; Ghezzi, A.
Abstract Background Fingolimod is approved by EMA as a second-line treatment for relapsing-remitting multiple sclerosis (RRMS). Experience with fingolimod in real life is still limited. Aim of our study was to report data on fingolimod effectiveness in a real life cohort of Italian active RRMS patients, naïve to second-line agents, followed for 2 years. Fingolimod was a part of the patients' regular treatment and is produced by Novartis. Methods We included all consecutive RRMS patients starting fingolimod at our center according to EMA criteria before January 1st 2013. Exclusion criteria were a previous treatment with natalizumab or an immunosuppressant therapy in the previous 12 months. All patients were clinically evaluated quarterly, and performed brain MRI yearly. Definition of "no evidence of disease activity" (NEDA-3): no relapses, no brain MRI activity and no 6-months confirmed worsening in EDSS score. Results We included 38 RRMS patients, 35 switched from first-line injectable therapies. Six patients were also previously treated with immunosuppressants (5 mitoxantrone, 1 cyclophosphamide). At 24th month 34 patients continued fingolimod treatment. Main adverse events were infections (18 %), liver-enzymes elevation (8 %), and leukopenia (8 %). After 12 and 24 months 79 and 63 % of patients were relapses-free. Fingolimod significantly reduced ARR compared to the previous year (0.3 ± 0.6 vs 1.2 ± 0.5;p < 0.001). After 12 and 24 months 63 and 37 % of patients had NEDA-3. Previous use of immunosuppressants and an ARR ≥1 in the 2 years predicted disease activity. Conclusion Fingolimod significantly reduce disease activity in active RRMS patients, with no severe/unexpected safety issues. Patients previously treated with immunosuppressants and with a higher ARR at baseline may respond less to fingolimod treatment.